Prognostic Effect of Microenvironment Phenotype in Triple-Negative Breast Cancer: Biomarker Analysis of a Prospective Trial - Zhu, Si-Yuan; Ma, Ding; Shao, Zhi-Ming; Yu, Ke-Da (Frontiers in Molecular Biosciences, 2021)
Background The microenvironment of triple-negative breast cancer (TNBC) can be divided into three clusters based on bioinformatics-based immunogenomic analysis: the "immune-desert" cluster, the "innate immune-inactivated" cluster, and the "immune-inflamed" cluster. The immune-inflamed cluster is considered as "hot tumor" while the other two are considered as "cold tumor". Methods To investigate the prognostic effect of microenvironment phenotypes on TNBC, we compared relapse-free survival (RFS) of different phenotypes in 100 patients with RNA sequencing-based expression data from the PATTERN trial (NCT01216111, published in JAMA Oncol 2020), which indicated a superior efficacy of adjuvant paclitaxel-plus-carboplatin regimen compared to the regimen of cyclophosphamide/epirubicin/fluorouracil followed by docetaxel for TNBC. We also analyzed the efficacy of the two regimens for different immune phenotypes to explore potential treatment strategies. Results No significant difference in RFS was observed between the "hot tumor" and the "cold tumor" (hazard ratio [HR]=0.68, 95% confidence interval [CI] 0.28-1.66, P=0.40). However, the "hot tumor" subtype was associated with significantly longer RFS in node-positive patients (HR=0.27, 95%CI 0.07-0.97, P=0.03). Consistently, a similar trend to improved RFS of the "hot tumor" phenotype was detected in patients with stage pT2-3 tumors (HR=0.29, 95%CI 0.06-1.30, P=0.08). Furthermore, no significant difference in RFS between the two treatment arms was observed in patients with "hot tumor" (HR=0.39, 95% CI 0.08-2.01, P=0.24) or "cold tumor" (HR=1.05, 95% CI 0.39-2.82, P=0.92). Conclusion The microenvironment phenotype in TNBC might have prognostic significance to patients with a high risk of recurrence. The association of the microenvironment phenotypes with the efficacy of adjuvant chemotherapy for TNBC remains to be further studied.